SPATIAL QUERY LOCALIZATION METHOD IN LIMITED REFERENCE POINT ENVIRONMENT: AN EMPIRICAL STUDY - Krebss, Viktors (European Scientific Journal, ESJ, 2014)
Intelligent Transport Systems (ITS) include telematics and all types of communications in vehicles, between vehicles (car-to-car), and between vehicles and fixed locations (car-to-infrastructure).ITS are advanced applications which, without embodying intelligence as such, aim to provide innovative services relating to different modes of transport and traffic management and enable various users to be better informed and make safer, more coordinated, and ’smarter’ use of transport networks. Knowing the correct positions of vehicle network nodes is essential to many application scenarios in the field of wireless sensor networks rely on positioning information. Various new localization and spatial analysis techniques has been introduced by modern geographic information system (GIS) technologies, using digital information, for which various digitized data creation methods are used. There has been a growing interest in the use of location-based spatial queries, which refer to a set of spatial queries that retrieve information based on mobile users’ current locations. The wireless environment and the communication constraints play an important role in determining the strategy for processing spatial queries. This article assumes simplest approach, a user establishes a point-to-point communication with the server so that her queries can be answered on demand. This paper gives an overview of the existing methods of localization and especially their applicability to wireless mobile networks and presents a study of how empirical ranging characteristics affect spatial query localization in wireless sensor networks. Then we study the spatial query selection, generic structure, and operation of localization algorithm for ad-hoc sensor networks on a simulation platform.